VP169 Grouping Treat-to-Target Studies In Systematic Reviews. (12th January 2018) - Hock, Emma; Wong, Ruth; Stevenson, Matt; Wailoo, Allan; Martyn-St James, Marrissa
Abstract : INTRODUCTION: A Health Technology Assessment (HTA) systematic review was undertaken in rheumatoid arthritis (RA) of treat-to-target (TTT) studies (n = 16) in which studies were grouped according to: TTT versus usual care, trials comparing different targets, or trials comparing different treatment protocols. To our knowledge, this was the first RA TTT review where studies were grouped in this way. We wanted to compare if our approach had been adopted in reviews of hypertension, hyperlipidemia or diabetes. METHODS: We searched MEDLINE for systematic reviews (SRs) of TTT studies in hypertension, hyperlipidaemia or diabetes. RESULTS: Eleven SRs were included; eight were in diabetes, and four were in hypertension, while none were in hyperlipidaemia. The diabetes SRs evaluated different insulin regimens (n = 3), non-insulin medications (n = 1), any antidiabetic treatment (n = 2), metformin monotherapy versus combination therapy (n = 1), and tight versus conventional glucose control (n = 1). The metformin review grouped studies by outcome whereas all other diabetes SRs grouped studies by treatment. Two hypertension SRs evaluated the effects of any treatment on two blood pressure targets, whereas one evaluated two different treatment regimen effects on the same blood pressure target. No SR in hypertension or diabetes included a mix of TTT versus usual care, and/or same treatment protocol different targets, and/or different treatment protocols same target study designs. CONCLUSIONS: In RA TTT does not refer to a single concept but a range of different approaches to the treatment of patients and the evidence reflects this. Whilst our approach to grouping RA TTT studies in a review was novel, this made it complex for us to synthesize evidence and draw general conclusions. We did not identify any TTT reviews in hypertension or diabetes including a mix of the TTT approaches we identified in RA. At present, a comparison of the strengths and limitations of our TTT review study grouping with reviews of hypertension, hyperlipidemia or diabetes cannot be made.